2020
DOI: 10.21037/tcr-20-751
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of radiation-related fibrosis based on the radiomic features of magnetic resonance imaging and computed tomography

Abstract: Background: To establish a predictive model for the fibrotic level of neck muscles after radiotherapy by using radiomic features extracted from the magnetic resonance imaging (MRI) before and after radiotherapy and planning computed tomography (CT) in nasopharyngeal carcinoma patients.Methods: A total of one hundred and eighty-six patients were finally enrolled in this study. According to the specific standard, all patients were divided into three different fibrosis groups. Regions of interests (ROI), includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Many clinical factors have been reported to influence the development of radiation pneumonia, including age, gender, smoking history, and history of chronic obstructive pulmonary disease (COPD). Wang et al reported that age was an influential factor in the development of radiation pneumonia and that patients of advanced age were at a higher risk of developing radiation pneumonia [5]. Tinkle et al showed that smoking history was a protective factor against radiation pneumonia and that smoking could prevent radiation pneumonia [3].…”
Section: Related Workmentioning
confidence: 99%
“…Many clinical factors have been reported to influence the development of radiation pneumonia, including age, gender, smoking history, and history of chronic obstructive pulmonary disease (COPD). Wang et al reported that age was an influential factor in the development of radiation pneumonia and that patients of advanced age were at a higher risk of developing radiation pneumonia [5]. Tinkle et al showed that smoking history was a protective factor against radiation pneumonia and that smoking could prevent radiation pneumonia [3].…”
Section: Related Workmentioning
confidence: 99%
“…The studies could be categorized into 4 domains, which were auto-contouring (n=21), 15 , 16 , 18 , 22 , 24 , 30–32 , 45–55 , 67 , 69 diagnosis (n=17), 10 , 15 , 16 , 23 , 26 , 27 , 49 , 52 , 54 , 56–63 prognosis (n=20) 12–14 , 17 , 19 , 25 , 28 , 29 , 33–44 and miscellaneous applications (n=7), 11 , 20 , 21 , 64–66 , 68 which included risk factor identification, image registration and radiotherapy planning ( Figure 2A ). Five studies examined both diagnosis and auto-contouring simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 12 , 15 , 26–28 , 35 , 43 , 44 , 49 , 54 , 56 , 60–63 Sensitivity was the most common studied parameter for diagnostic performance: 15 out of 23 papers. 10 , 15 , 16 , 23 , 26 , 27 , 49 , 52 , 54 , 56 , 59–63 The specificity was only reported for prognosis (n=7) 12 , 14 , 28 , 34 , 39 , 40 , 43 and diagnosis (n=15). 10 , 15 , 16 , 23 , 26 , 27 , 49 , 52 , 54 , 56 , 59–63 In addition, the DSC (n=20) 15 , 18 , 22 , 24 , 30–32 , 45–53 , 55 , 65 , 67 , 69 and ASSD (n=10) 18 , 22 , 24 , 31 , 32 , 45 , 46 , 48 , 51 , 69 were the primary metrics reported in studies on auto-contouring ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations